Assessment of reptile species in the seven falls of Barangay Lake Lahit, Municiplaity of Lake Sebu, South Cotabato - Faldas, Scott Lester Pacinabao (2008)
An inventory of the reptile in the seven falls of Barangay Lake Lahit in Lake Sebu was conducted to generate baseline information on reptiles inhabiting the area. Collection was done per falls during the months of May and October 2007. A total of 18 species consisted of 9 snake species and 9 lizard species were catalogued and identified to the following families: agamidae, Scincidae, and Varanidae for lizards and Viperidae, Elapidae, and Colubridae for snakes. Results showed high diversity of reptiles that also had high endemism (61.11%) which included a few rare, threatened, and endangered species. The study showed the different microhabitats inhabited by the different species of reptiles. Possible threats to the reptile diversity in the area were also identified. These included rapid development in the area leading to habitat fragmentation, snake killings out of fear, possible pollution of the water of the falls, agricultural practices in the borders of the seven falls, and other anthropological disturbances that may affect the reptile diversity of the area. The study may serve as a guide for future bio-ecological studies of reptiles in the local forest area
Thesis (BS Biology) -- University of the Philippines Mindanao, 2008
Keywords: Reptiles; Reptiles -- Species; Reptiles -- Habitat; Ethnobiology; Reptiles -- Conservation efforts; Reptiles -- Detremination of threats; Philippine reptile diversity; Megadiversity; Reptile species -- Barangay Lake Lahit, Lake Sebu -- South Cotabato -- Mindanao -- Philippines; Barangay Lake Lahit, Lake Sebu; Barangay Lake Lahit, Lake Sebu -- South Cotabato -- Mindanao -- Philippines